Effect of different concentration of moringa leaf extract (MLE) on proximate components, cooking loss, pH and color attributes of broiler meat sausage batter - Kabir, MH; Ahmmed, A; Hashem , MA; Ali, MS (Meat Research, 2025)
This study investigated the effects of varying concentrations of Moringa leaf extract (MLE) on the proximate composition, cooking loss, pH, and color attributes (CIE L*, a*, b*) of broiler meat sausage batter. Employing a 3x5 factorial design, the study incorporated various storage periods (0, 14, and 28 days) and treatment groups (control, BHT, and MLE at 0.5%, 1.0%, and 1.5%). Results demonstrated that 1.5% MLE significantly reduced cooking loss (14.73 ± 0.97%) and improved protein retention (21.54 ± 0.07%) compared to the control group, which exhibited a cooking loss of 19.07 ± 3.11% and protein retention of 18.49 ± 1.49%. Additionally, MLE significantly influenced pH, reducing it from 6.69 in the control to values ranging from 6.27 to 6.33 in the treated samples (p < 0.01), while influencing color parameters by increasing yellowness (b = 23.85 at 1.5% MLE) and decreasing redness (a = −2.82). Proximate components, including dry matter, ash, protein, and fat, as well as cooking loss, remained unaffected (p > 0.05). Notably, MLE at a 1.0% concentration was identified as optimal, enhancing antioxidant properties without compromising sensory or nutritional quality. These findings underscore the potential of MLE as a functional, natural ingredients in clean-label meat products, catering to the growing consumer demand for alternatives to synthetic additives aimed at improving the quality and shelf life of broiler meat sausages.